MECHANISMS FOR UTILIZING EUROPEAN EXPERIENCE IN PUBLIC-PRIVATE PARTNERSHIP FOR THE DEVELOPMENT OF VOCATIONAL EDUCATION IN UKRAINE (Innovative professional education, 2024)
The article reveals the mechanisms of using the European experience of public-private partnership in the development of professional education in Ukraine, namely: taking into account successful models of public-private partnership in the field of professional education and training in the countries of the European Union; forms of involvement of the private sector in the development of educational programs, investment in the construction and modernization of the material and technical base of educational institutions, and the development of the professional competence of teachers of vocational education. Recommendationsfor the development of public-private partnership in the field of professional education of Ukraine, taking intoaccount the progressive European experience, are proposed.
Keywords: european experience, legislation, investment, educational programs, private sector, professional competence, vocational education, public-private partnership